Optimizing the Development of Online Appointment System for Dental Clinics through Agile Methodology Implementation - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research addresses the problem of optimizing the development process of an online appointment system for dental clinics. The study focuses on implementing Agile methodology to improve collaboration, change responsiveness, and the overall value delivered to users. The methodology involves iterative testing and gathering user feedback to ensure better alignment with user needs and expectations. The study's findings highlight the significant benefits of Agile methodology in en-hancing system acceptance and flexibility in addressing challenges during development. The research contributes to the understanding and application of Agile methodology in healthcare system develop-ment, particularly in improving the effectiveness and responsiveness of dental healthcare services through information technology.